Mechanisms of gradual pressure drop in angiographically normal left anterior descending and right coronary artery: Insights from wave intensity analysis. Issue 1 (July 2021) - Tamaru, Hiroto; Fujii, Kenichi; Fukunaga, Masashi; Imanaka, Takahiro; Kawai, Kenji; Miki, Kojiro; Horimatsu, Tetsuo; Nishimura, Machiko; Saita, Ten; Sumiyoshi, Akinori; Shibuya, Masahiko; Masuyama, Tohru; et al.
Highlights: Coronary pressure gradually decreased across the length of the left anterior descending artery (LAD) but not the right coronary artery (RCA). The backward-traveling suction wave decreased through the length of the LAD. The change in the backward suction wave correlated with myocardial territory size. All wave intensity parameters were constant throughout the length of the RCA. Abstract: Background: This study evaluated the mechanism of decline in coronary pressure from the proximal to the distal part of the coronary arteries in the left anterior descending (LAD) versus the right coronary artery (RCA) from the insight of coronary hemodynamics using wave intensity analysis (WIA). Methods: Twelve patients with angiographically normal LAD and RCA were prospectively enrolled. Distal coronary pressure, mean aortic pressure, and average peak velocity were measured at 4 different positions: 9, 6, 3, and 0 cm distal from each coronary ostium. Results: The distal-to-proximal coronary pressure ratio during maximum hyperemia gradually decreased in proportion to the distance from the ostium (0.92±0.03 and 0.98±0.03 at 9 cm distal to the LAD and RCA ostium). WIA showed the dominant forward-traveling compression wave gradually decreased and the backward-traveling suction wave gradually decreased in proportion to the decrease in coronary pressure through the length of the non-diseased LAD but not the RCA. Conclusions: The pushing wave and suction wave intensities on WIA were diminished in proportion to the distance from the ostium of the LAD despite the wave intensity not changing across the length of the RCA, which may lead to gradual intracoronary pressure drop in the angiographically normal LAD.